March on the Barbados Telephone Company - (:unkn) unknown (My University, 2012)
Representatives of the Barbados Workers Union marching through Broad Street en route to the headquarters of the Barbados Telephone Co. Ltd. in support of worker, David Giles. The Barbados Telephone strike of 1981 was one of the BWU's more intense industrial relations battles. Here General Secretary Frank Walcott together with his team strides determinedly into action. The back of the photograph carries handwritten notes indicating the names of those leading the march, including Burns Bonadie, Secretary Treasurer of the CCL [Caribbean Congress of Labour]
Portrait; Black and white
Keywords: Walcott, Frank, Sir 1916-; Trotman, Roy, Sir; Daniel, Lemuel; Scott, Orlando; Bonadie, Burns; Williams, John; Giles, David; Barbados Workers Union; Barbados Telephone Co.; Demonstrations; Labor Unions; Strikes; Photographs; Barbados--Bridgetown--Broad Street; January 1981